2019
DOI: 10.1097/01.apo.0000580140.74826.f5
|View full text |Cite
|
Sign up to set email alerts
|

Astigmatism Correction Using SMILE

Abstract: Small incision lenticule extraction (SMILE) was introduced in the recent decade for the treatment of myopia and myopic astigmatism. This flap-free technique has a high efficacy and safety profile and also carries potential advantages over laser in situ keratomileusis such as a better corneal biomechanical stability, reduction in dry eyes rate, and the avoidance of flap complications. However, there have been concerns regarding the precision of astigmatism correction that undercorrection has been reported to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…For astigmatism correction, the Visumax software (Carl Zeiss Meditec) adds a transition zone to convert the elliptical lenticule into a circle. However, the lenticule still has an oval posterior surface, which results in a smaller diameter of the cleavage plane along its steep axis that its flat axis [ 20 ]. Hou et al speculated that local curvature changes and wound healing caused by the superior incision location may be related to the asymmetric change in horizontal and vertical orientation [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…For astigmatism correction, the Visumax software (Carl Zeiss Meditec) adds a transition zone to convert the elliptical lenticule into a circle. However, the lenticule still has an oval posterior surface, which results in a smaller diameter of the cleavage plane along its steep axis that its flat axis [ 20 ]. Hou et al speculated that local curvature changes and wound healing caused by the superior incision location may be related to the asymmetric change in horizontal and vertical orientation [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that there is a slight tendency toward undercorrection when treating astigmatism with SMILE [ 4 , 8 , 19 , 20 ]. Ivarsen and Hjortdal [ 21 ] reported an undercorrection of 13% per diopter of attempted cylinder correction in low astigmatic eyes (< 2.5 D) and 16% per diopter in highly astigmatic eyes (≥2.5 D) after SMILE; they believed that the greater the preoperative astigmatism, the higher the degree of undercorrection.…”
Section: Discussionmentioning
confidence: 99%
“…As the corneal healing response stabilized at 3 Axis shift was determined from the postoperative to preoperative cylinder axis a Shifts were determined as 0 for eyes with zero residual cylinder magnitude months, the axis of astigmatism mostly reversed, but the overall axis deviation of astigmatism was small. Some studies have shown that there is a slight tendency toward undercorrection when treating astigmatism with SMILE [4,8,19,20]. Ivarsen and Hjortdal [21] reported an undercorrection of 13% per diopter of attempted cylinder correction in low astigmatic eyes (< 2.5 D) and 16% per diopter in highly astigmatic eyes (≥2.5 D) after SMILE; they believed that the greater the preoperative astigmatism, the higher the degree of undercorrection.…”
Section: Discussionmentioning
confidence: 99%